KNOWLEDGE AND ATTITUDES OF THE COMMUNITY TOWARDS MALARIA PREVENTION IN PASIRBIDANG VILLAGE, CENTRAL TAPANULI REGENCY IN 2021 - Syahrul Khairati; Leli Desi Uli Basana; Ermia Gulo (Institute of Computer Science (IOCS), 2022)
Indonesia is one of the countries in the world that still faces the risk of Malaria. Sarudik Subdistrict is one of the Malaria endemic areas in Central Tapanuli Regency with an Annual Parasite Incidence (API) rate in 2015 of 10.93%. The incidence of malaria is caused by direct contact between female Anopheles mosquitoes and humans and is supported by community behavior. This type of research is a descriptive research that aims to find out the knowledge and attitudes of the community towards malaria prevention in Pasir Village, Central Tapanu Regency. This research was conducted in May 2021. The population in this study was 1,282 households, the sample was obtained by 93 respondents. The data used are primary data and skunder data. The analyzed data descriptively are presented in the frequency distribution table.